Lunatic Asylum, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Exterior view of the asylum which is surrounded by many trees.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asylums--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Psychiatric hospitals--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. Ann's; Mental health facilities--Trinidad and Tobago; Specialty hospitals--Trinidad and Tobago; Architecture--Trinidad and Tobago